Calibrating 30 years of experimental research: a meta-analysis of the atmospheric effects of music, scent, and color - Roschk, H.; Loureiro, S. M. C.; Breitsohl, J. (Journal of Retailing, 2017)
Atmospheric in-store stimuli have been the subject of considerable empirical investigation for over 30 years. This research presents a meta-analysis of 66 studies and 135 effects (N = 15,621) calibrating the atmospheric effects of music, scent, and color on shopping outcomes. At anaggregate level, the results reveal that environments in which music or scent are present yield higher pleasure, satisfaction, and behavioral intentionratings when compared with environments in which such conditions are absent. Warm colors produce higher levels of arousal than cool colors,while cool colors produce higher levels of satisfaction than warm colors. The estimated average strength of these relationships ranged from smallto medium. Effect sizes exhibited significant between-study variance, which can be partly explained by the moderators investigated. For instance,larger effect sizes were observed for the relationship between scent and pleasure in those samples with a higher (vs. lower) proportion of females.Data also indicated a tendency toward stronger music and scent effects in service settings as compared to retail settings. The results of this analysis,based on data aggregated across the research stream, offer retailers a guide to enhance customers’ shopping experience through judicious use ofin-store atmospheric stimuli.